Digital Curation, AustLit, and Australian Children's Literature. Issue 1 (July 2019) - Cross, Amy; Allan, Cherie; Kilner, Kerry
Abstract : This paper examines the effects of curatorial processes used to develop children's literature digital research projects in the bibliographic database AustLit. Through AustLit's emphasis on contextualising individual works within cultural, biographical, and critical spaces, Australia's literary history is comprehensively represented in a unique digital humanities space. Within AustLit is BlackWords, a project dedicated to recording Australia's Aboriginal and Torres Strait Islander storytelling, publishing, and literary cultural history, including children's and young adult texts. Children's literature has received significant attention in AustLit (and BlackWords) over the last decade through three projects that are documented in this paper. The curation of this data highlights the challenges in presenting 'national' literatures in countries where minority voices were (and perhaps continue to be) repressed and unseen. This paper employs a 'resourceful reading' approach – both close and distant reading methods – to trace the complex and ever-evolving definition of 'Australian children's literature'.